Maintenance Efforts of Bali Culture and Language Through Local Content in Primary Schools - Ketut Susiani (Bisma The Journal of Counseling, 2021)
This study uses a qualitative case study approach, which is a study that aims to describe a condition that is happening in the real world. The research procedure adopted the case study research procedure by Yin which includes (1) design the case study protocol; (2) Conduct the case study; (3) Analyze case study evidence: and (4) Develop conclusions, recommendations, and implications based on the evidence. The subjects of this study were elementary school teachers and students, and school documents were examined related to the maintenance of Balinese culture and language through local content carried out in schools. The data collection technique was carried out by structured interviews using interview guidelines related to maintaining Balinese language culture and Balinese local content. Observations were made with a participatory observation approach, and documentation studies were carried out by collecting documents related to the maintenance of Balinese culture and Balinese language in schools. Qualitative data analysis techniques began with grouping data based on primary data sources and secondary data. The results of this study indicate that the application of local content in elementary schools is one of the contents that can be used in maintaining, preserving and preserving the Balinese language culture in schools. The results of surveys, observations and interviews at SD Buleleng indicate that the maintenance of Balinese culture and language has many weaknesses, seen from the use of local languages that are not used in communication and Balinese culture which is fading due to the influence of other cultures. This can be seen in the language used in schools not using Balinese in daily communication in the sense that many do not understand the meaning of the Balinese language used because SOR is Singgih Bahasa. The results of study have and important implication to the teaching learning contents of Balinese language in elementary school in Bali, Indoensia.